A Profile of Care Coordination, Missed School Days, and Unmet Needs Among Oregon Children with Special Health Care Needs with Behavioral and Mental Health Conditions. - Lindly, Olivia J.; Martin, Alison J.; Lally, Kathryn (Community Mental Health Journal, 2020)
To inform Oregon's Title V needs assessment activities, we aimed to (1) characterize the state's subpopulation of children with special health care needs (CSHCN) with behavioral and mental health conditions (B/MHC) and (2) determine associations of care coordination with missed school days and unmet needs for this subpopulation. We analyzed 2009–2010 National Survey of Children with Special Health Care Needs data on 736 Oregon CSHCN < 18 years, including 418 CSHCN with B/MHC. Among Oregon CSHCN with B/MHC: 48.9% missed ≥ 4 school days, 25% had ≥ 1 unmet health services need, and 14.8% had ≥ 1 unmet family support services need. Care coordination was associated with lower adjusted odds of ≥ 1 unmet health services need but was not significantly associated with missed school days or unmet family support services need. The approach to identify Oregon CSHCN with B/MHC may be adopted by other states endeavoring to improve health for this vulnerable subpopulation.